(untitled) (Research, Society and Development, 2023)
Autism Spectrum Disorder (ASD) is associated with a neurobiological alteration that causes persistent deficits in communication and social interaction, in multiple contexts, in addition to the presence of restricted and repetitive patterns of behavior, interests or activities, which can occur in levels of severity different. As the school is a reference environment for the development of children and adolescents, it is seen as a fundamental point of support not only for the student with ASD, but for their entire family. Since the last years of the 20th century, there has been a progression in relation to educational normative acts, with different interpretations of concepts around the inclusion of students with disabilities in formal education. The municipality of Gurupi is the third largest in the State of Tocantins and is considered the center of the southern region of the State. Thus, this research has the following question as problematic: What is the influence of children’s literature on the inclusion of students with autism in public schools in Gurupi - TO? Bringing children’s literature to the inclusive education scenario, specifically for children with ASD, means offering children experiences that develop imagination, emotions and feelings, also contributing to an inclusive discourse, breaking paradigms of limitations. It is concluded that within the data evaluated, the municipality of Gurupi is lacking in the requirement of specific children’s literature for individuals with autism spectrum disorder.